Konsep Kebersihan dalam Al-Qur’an Menurut Hamka: Integrasi Dimensi Spiritual dan Fisik dalam Tafsir Al-Azhar - Siti Mardiana Harahap (Yayasan Albahriah Jamiah Indonesia, 2026)
The concept of cleanliness in the Qur’an holds a fundamental position as the basis for the formation of individual and social ethics. At the same time, contemporary exegetical studies still tend to separate the spiritual and physical dimensions, resulting in partial understandings. This paper aims to examine the concept of cleanliness in Hamka’s Tafsir al-Azhar integratively to construct a meaning that unites both dimensions within a complete epistemological framework. The method used is a qualitative approach based on literature studies with thematic interpretation techniques and a hermeneutic-contextual approach to interpret the verses on cleanliness comprehensively. The results of the analysis show a conceptual integration of external and internal cleanliness through an emphasis on the purity of the soul, disciplined worship, and social responsibility, as reflected in daily practice. Hamka’s interpretation constructs cleanliness as a multidimensional value system that connects personal ethics, physical health, and transcendental awareness in a mutually reinforcing unity. This integration demonstrates an interpretive orientation that is both contextual and normative, with strong relevance to modern problems such as environmental degradation and moral crisis. The academic implications confirm Hamka’s significant contribution to the development of integrative interpretation studies that connect normative, ethical, and practical dimensions, while enriching the hermeneutic approach in understanding the Qur’an holistically and contextually.